A Qualitative Study on the Turnover Intention of the New Generation of Rural Teachers from the Perspective of Relational Being - JIANG Min; KANG Haiyan (Jiaoshi jiaoyu xuebao)
The new generation of rural teachers are becoming the main force in rural education. Its loss will lead to a lack of successors for rural education, thereby affecting the improvement of educational quality. This study adopts Kenneth J. Gergen's Relational Being theory as its theoretical framework, starting from three focal points: the exemplary behavior of others, the diversity of self-roles, and previous interaction scripts. Using non-probability sampling, eight new-generation rural teachers were selected as research subjects to conduct qualitative analysis of their intention to leave. The findings reveal that these new-generation rural teachers face three relational dilemmas: the absence of role models, conflicts in interaction arising from multiple roles, and deviations from the previous interactive script. Based on these findings, the analysis identifies key causes of their turnover intention: narrow professional interaction platforms, the limited nature and traction of relationships, and the lack of social identity in rural areas. To address the turnover intention among new-generation rural teachers, the following strategies are proposed: broadening interaction channels and setting examples; leveraging the leadership of principals to create learning communities; and taking root in rural society to enhance cultural confidence.